The Concept of Restorative Justice in Criminal Procedure Law through The Rehabilitation Process: Integrated Assessment at The National Narcotics Agency of Bone Regency - Muljan, Muljan; Nawawi, Jumriani (Al-Bayyinah, 2023)
The study discusses the "Concept of Restorative Justice in Criminal Procedure Law through Rehabilitation Process by the Integrated Assessment Team at the National Narcotics Agency of Bone Regency." The research aims to: identify the essence of Restorative Justice through Rehabilitation by the Integrated Assessment Team at the National Narcotics Agency of Bone Regency, describe the implementation of Restorative Justice through Rehabilitation by the Integrated Assessment Team at the National Narcotics Agency of Bone Regency, and analyze the integration of Competency Development in Criminal Procedure Law courses through the Concept of Restorative Justice in Rehabilitation by the Integrated Assessment Team at the National Narcotics Agency of Bone Regency. This research employs a qualitative approach with legislative, case, and conceptual approaches located at the National Narcotics Agency of Bone Regency, with doctors and the rehabilitation section of BNNK Bone as the sources of information, who are part of the integrated assessment team. The data used are primary data obtained through interviews, observation, and documentation. The research findings indicate that: (1) The essence of Restorative Justice through Rehabilitation by the Integrated Assessment Team at the National Narcotics Agency of Bone Regency is rooted in the protection of the health and social life of drug abusers specifically and society in general. (2) The implementation of Restorative Justice through Rehabilitation by the Integrated Assessment Team at the National Narcotics Agency of Bone Regency complies with regulations, but there are still some challenges, including ambiguous regulations, law enforcement officers' paradigm towards rehabilitation, and inadequate rehabilitation facilities; (3) The integration of Competency Development in Criminal Procedure Law courses through the Concept of Restorative Justice in Rehabilitation by the Integrated Assessment Team at the National Narcotics Agency of Bone Regency can be applied to related criminal law courses through sub-topics in the semester lesson plan, especially regarding narcotics offenses.